2011
DOI: 10.3109/07435800.2011.580443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insulin-Like Growth Factor-1 in Indian Growth Hormone-Deficient Children on Growth Hormone Therapy

Abstract: The change in serum IGF-1 z-scores in response to GHT in Indian children may not be a good indicator for monitoring growth hormone responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
4
1
Order By: Relevance
“…Khadilkar et al [ 15 ] reported a similar mean IGF-1 of 84.09 ng/ml but higher mean IGF-1 SDS (−0.86) with a lower mean peak GH (0.71 ng/ml). A disparity from our result was observed by Ekbote et al ,[ 21 ] who reported a much lower mean IGF-1 (20 ng/ml), mean IGF-1 SDS (−3.40), and lower mean peak GH value (0.97 ng/ml) in IGHD patients. The contrast in findings may be explained by considering the fact that these studies included both IGHD and MPHD patients in the analysis and included only a small number of participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Khadilkar et al [ 15 ] reported a similar mean IGF-1 of 84.09 ng/ml but higher mean IGF-1 SDS (−0.86) with a lower mean peak GH (0.71 ng/ml). A disparity from our result was observed by Ekbote et al ,[ 21 ] who reported a much lower mean IGF-1 (20 ng/ml), mean IGF-1 SDS (−3.40), and lower mean peak GH value (0.97 ng/ml) in IGHD patients. The contrast in findings may be explained by considering the fact that these studies included both IGHD and MPHD patients in the analysis and included only a small number of participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Poor standardization of these assays in commercial laboratories in India is yet another limitation. Although normative IGF-1 data for Indian children has been derived, it is seldom used in commercial laboratory reports [25]. …”
Section: Resultsmentioning
confidence: 99%
“…There are several studies on the effects of growth hormone on short stature from India,[ 5 9 11 12 13 14 15 16 ] but none have compared the outcomes among different age groups to ascertain the maximum benefits [ Table 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our study, the mean age of initiation of growth hormone in the Indian studies range from 8 to 13 yrs. [ 9 11 12 13 14 15 16 ] Early initiation resulted in better height outcomes and also proved to be financially better for the Indian parents as the cost is lesser in younger children due to lower doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation